Peningkatan Produksi ASI pada Ibu Hamil - Fitriani Ningsih; Rizki Muji Lestari; Siti Santy Sianipar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
In breastfeeding, not all mothers can breastfeed exclusively. One of the main obstacles is the physical and psychological conditions of the postpartum mother. The low self-confidence of the mother about the success of breastfeeding can reduce the production of mother's milk. This condition greatly inhibits the release of breast milk, so that it impacts the risk of failure to achieve exclusive breastfeeding. The purpose of this activity is carried out as an effort to prepare pregnant women in the third trimester of exclusive breastfeeding. The methods used in this activity are lectures, demonstrations, and practices. The results of this activity were attended by 30 pregnant women in the third trimester. During the activity, the mothers were very enthusiastic; this was evident in the increase in their knowledge before and after being given information. In addition, during the hypnobreastfeeding and massage oxytocin training, the mother seemed comfortable and relaxed when participating in this activity